Leader-follower formation control of nonholonomic mobile robots subject to robots failure - Abdul-razaq, Yusuf; Marquez, Horacio J (International journal of advanced robotic systems, 2024)
Over the years, control of autonomous vehicles in a defined formation has been the subject of much research. Albeit leader-follower approach being one of the most used in formation control, it suffers a major practical drawback of leader failure while cruising in formation. In this work, we aim to solve this problem by proposing a novel assignment algorithm that assigns a new leader from the follower robots to ensure robots complete their given task when their leader fails. This algorithm also assign role to new robots joining the group, as well as the failed robot when rescued back to the team. We drive robots towards their desired trajectories to achieve formation using a Lyapunov-based time-varying state tracking controller from the literature. Due to role switching amongst member robots, we propose a new variant of the limit-cycle obstacle avoidance algorithm to ensure smooth and collision free transition. Simulations and experiments are performed using the robot operating system framework due to its flexibility to verify the effectiveness and reliability of the proposed algorithms.